Vertical Partnerships Between OEM And First Tier: Lessons From Automotive Component Companies In Greater Jakarta-Indonesia - Syah, Donny Oktavian; Lupiyoadi, Rambat; Suryani, Embun (The South East Asian Journal of Management, 2022)
Research Aims: This research aimed to investigate vertical partnerships between Original Equipment Manufacturers (OEMs) and first-tier automotive component firms based on the relationships between technology transfer, technical exchange, government role and supplier performance in the Greater Jakarta area. Design/Methodology/Approach: A total of 65 respondent firms participated, comprising 6 OEMs and 59 first-tier firms. The research included site visits and interviews with companies based on questionnaires completed by representative individuals from middle management upward with responsibility for assessing product quality (purposive sampling). The questionnaire results were measured using Partial Least Squares Path Modelling (PLS-PM). Research Findings: The results highlighted significant relationships between government role and technology transfer (p-value = 0.00), government role and supplier performance improvement (p-value = 0.017), and technical exchange and supplier performance improvement (p-value = 0.077). However, no significant relationship was found between technology transfer and supplier performance improvement (p-value = 0.353). Theoretical Contribution/Originality: Understanding the vertical relations between OEMs and first-tier automotive component firms in Indonesia. Managerial Implications in the South East Asian Context: Solid relationships between OEMs and first-tier companies in Greater Jakarta, Indonesia are especially triggered by the increasing tendency for local component use (TKDN/Domestic Component Level). Research limitation & Implications: The research examined vertical relationships between OEMs and first-tier firms, notably between technology transfer and supplier performance improvement, technical exchange and supplier performance improvement, government role and technology transfer, and government and supplier performance improvement.